Edukacja demokratyczna i humanistyczna jako ruch i dzieło społeczne - Kwieciński, Zbigniew (Wydawnictwo Naukowe UAM, 2014)
The text is a revised version of a paper delivered at a conference in Jabłonna in November 1981 during the Solidarity revolution, put down by the introduction of martial law in Poland in December that year. The author asks about the fundamental causes of this social and political shake-up and about the implications for the future of the education system. He scrutinizes the demands of different social and scientific circles which debated on the future of education. He proposes and foresees the possibility of limiting the role of the state, or the socialization of education, i.e. its independent creation by parents, teachers, local and regional communities and instilling in the learners of the skill to develop an inner autonomy and wide humanistic horizons. He enumerates many difficult dilemmas to be solved within these processes, stressing the need for long-term, consistent action.
Democratic and Humanistic Education as Movement and Social Undertaking
Keywords: essence of the shake-up of 1980-1981; social claims towards education; socialization ofthe subject of change (limiting the role of the state) and humanization of content and processes; dilemmas and aporias of change in education